A surfacing flux-cored welding wire and its preparation method and use

By using surfacing flux core welding wire, the existing surfacing welding rods have solved the problems of high dust, high labor intensity, and easy looseness and pores in the welding layer metal, so as to achieve no pores in the weld, good welding process and welding The high strength, high toughness, high wear resistance and excellent corrosion resistance of the seam metal extends the service life of the valve.

CN115592296BActive Publication Date: 2025-02-14SHANDONG JULI WELDING CO LTD +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211253141.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-13
Publication Date
2025-02-14
Estimated Expiration
2042-10-13

AI Technical Summary

Technical Problem

The existing surfacing welding rods are dusty during the welding process, and the labor intensity is high, and the metal of the welding layer is prone to loosening and pores and other tissue defects.

Method used

The welding wire is made of a steel strip and a flux core filled in the steel strip. The flux core includes metal chromium, manganese metal, quartz, rutile, ferrosilicon, potassium titanate, fluorite, ferrosilicon, ferromolybdenum, vanadium Components such as iron, iron tungsten, rare earth oxides, etc. can improve the strength of the weld and the resistance to high-temperature corrosion by adjusting alloy elements and adding rare earth oxides.

Benefits of technology

Under the action of gas and protective agent, the weld has no pores and good welding process. The weld metal has high strength, high toughness, high wear resistance and excellent corrosion resistance, extending the service life of the valve.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115592296B_ABST
    Figure CN115592296B_ABST
Patent Text Reader

Abstract

The present invention provides a surfacing flux-cored welding wire and a preparation method and use thereof, and specifically relates to the technical field of welding materials. The surfacing flux-cored welding wire of the present invention comprises a steel strip and a flux core filled in the steel strip, and is characterized in that, in terms of the mass percentage of the flux core, the flux core comprises the following components: 30-40% of metal chromium, 2-5% of metal manganese, 5-6% of quartz, 25-30% of rutile, 3-5% of ferrosilicon, 5-10% of potassium titanate, 5-10% of fluorite, 2-2.5% of ferromolybdenum, 0.1-0.2% of ferrovanadium, 1-2% of ferrotungsten, 1% of rare earth oxide, and the balance is iron powder. The surfacing flux-cored welding wire of the present invention has good wear resistance and corrosion resistance, and the weld has no pores in the absence of gas and protective agent, and is suitable for surfacing of valve sealing surfaces, which can improve its surface wear resistance and corrosion resistance, thereby extending the service life of the valve.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of welding materials, and in particular to a surfacing flux-cored welding wire and a preparation method and application thereof. Background Art

[0002] High temperature and wear-resistant valves are mainly used in the fields of energy and chemical industry, and are used in critical occasions with extremely harsh working conditions. The working temperature of the valve is often greater than 400℃, and it is eroded by the fluid and corroded by the medium. In addition, the valve is frequently opened and closed. Once the valve sealing surface leaks, it will cause significant economic losses and seriously threaten the safety of production personnel. This requires the valve sealing surface to have excellent corrosion resistance, wear resistance, and high temperature resistance. The sealing surface is the most critical working surface of the valve product, and the quality of the valve sealing surface is related to the service life of the valve. Surfacing welding of the valve sealing surface is a key process in valve production. A layer of wear-resistant and corrosion-resistant material is applied on the valve sealing surface to avoid or reduce the losses caused by wear and corrosion to extend the service life of parts and equipment, thereby improving production efficiency.

[0003] In the prior art, cladding materials are usually cladding electrodes, which are labor-intensive, produce a lot of smoke and dust, are harmful to the human body, and the cladding layer metal is prone to looseness, pores and other structural defects. Summary of the invention

[0004] In view of the above shortcomings of the prior art, the present invention provides a cladding flux-cored welding wire and a preparation method and use thereof, so as to improve the problems of excessive dust and easy loosening of metal during cladding electrode welding.

[0005] To achieve the above-mentioned purpose and other related purposes, the present invention provides a surfacing flux-cored welding wire, which comprises a steel strip and a flux core filled in the steel strip, wherein the flux core comprises the following components in percentage by mass: 30-40% metallic chromium, 2-5% metallic manganese, 5-6% quartz, 25-30% rutile, 3-5% ferrosilicon, 5-10% potassium titanate, 5-10% fluorite, 2-2.5% ferromolybdenum, 0.1-0.2% ferrovanadium, 1-2% ferrotungsten, 1% rare earth oxide, and the balance is iron powder.

[0006] In an example of the present invention, the weight of the flux core in the cladding flux-cored welding wire is 18% to 19% of the total weight of the cladding flux-cored welding wire.

[0007] In one example of the present invention, the particle size of the drug core is 40-80 meshes.

[0008] In an example of the present invention, the ferrosilicon is 75# ferrosilicon, the silicon content of the 75# ferrosilicon is greater than or equal to 72%, the phosphorus content is less than or equal to 0.04%, and the sulfur content is less than or equal to 0.02%.

[0009] In an example of the present invention, the calcium fluoride content in the fluorite is greater than or equal to 95%, the silicon dioxide content is less than or equal to 4.5%, the phosphorus content is less than or equal to 0.03%, and the sulfur content is less than or equal to 0.03%.

[0010] In an example of the present invention, the rare earth oxide includes ceria.

[0011] In an example of the present invention, the steel strip is a carbon steel strip.

[0012] The invention provides a preparation method of a cladding flux-cored welding wire, comprising the following steps: uniformly mixing the above-mentioned components to configure a flux core; longitudinally shearing, wrapping, cleaning, and then rolling a steel strip into a U-shaped groove; filling the flux core into the U-shaped groove; closing, reducing the diameter, drawing, and winding the steel strip filled with the flux core to obtain the cladding flux-cored welding wire.

[0013] The present invention also provides a use of a surfacing flux-cored welding wire, wherein the surfacing flux-cored welding wire is used for surfacing welding of valve sealing surfaces.

[0014] The surfacing flux-cored welding wire of the present invention improves the strength of the weld metal by adjusting alloy elements such as molybdenum, tungsten, and vanadium; the addition of rare earth oxides can improve the high-temperature corrosion resistance and impact toughness of the weld metal; the addition of quartz and rutile can form a short slag effect, which is conducive to the formation of the weld; the application of potassium titanate ensures good weld formation, stable arc, smooth welding and other welding process properties. This welding wire is used for surfacing welding of valve sealing surfaces, which can improve its surface wear resistance and corrosion resistance, thereby extending the service life of the valve. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0016] Figure 1 The present invention is a flow chart of the preparation method of the cladding flux-cored welding wire. DETAILED DESCRIPTION

[0017] The following is an explanation of the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the features in the following embodiments and the embodiments can be combined with each other without conflict. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods for which specific conditions are not specified in the following examples are usually carried out under conventional conditions or according to the conditions recommended by the manufacturers.

[0018] The invention provides a surfacing flux-cored welding wire and a preparation method and application thereof. The surfacing flux-cored welding wire has good wear resistance and corrosion resistance, can produce a weld without pores in the absence of gas and protective agent, and can be suitable for surfacing of valve sealing surfaces.

[0019] The surfacing flux-cored welding wire of the present invention comprises a steel strip and a flux core filled in the steel strip, wherein the flux core comprises the following components, measured by mass percentage, 30-40% of metallic chromium, 2-5% of metallic manganese, 5-6% of quartz, 25-30% of rutile, 3-5% of ferrosilicon, 5-10% of potassium titanate, 5-10% of fluorite, 2-2.5% of ferromolybdenum, 0.1-0.2% of ferrovanadium, 1-2% of ferrotungsten, 1% of rare earth oxide, and the balance is iron powder.

[0020] The functions of the components in the flux core of cladding flux-cored wire are as follows:

[0021] Metal chromium: an alloying element that transitions into the weld metal, improves hardenability, produces solid solution strengthening, forms Cr7C3 and Fe7C3 (M7C3) stable carbides, and increases the wear resistance of the weld. Chromium has the effect of promoting secondary hardening effect (replacing Mo in Mo2C to form (Mo, Cr)2C), forming a fine dispersed precipitate phase, and can improve hardness and tensile yield strength. The mass percentage of metal chromium in the present invention is 30-40%, for example, the mass percentage of metal chromium can be any value within the above range such as 30%, 33%, 38%, 40%, etc.

[0022] Ferrosilicon: deoxidizes, accelerates the melting of welding wire, improves the fluidity of slag, reduces the sensitivity of weld porosity; transitions alloy elements into weld metal. The mass percentage of ferrosilicon in the present invention is 3-5%, for example, the mass percentage of ferrosilicon can be any value within the above range such as 3%, 4% or 5%.

[0023] Metallic manganese: deoxidizer, and also a transitional alloy element to the weld metal. Manganese is an element that stabilizes austenite, reduces the starting temperature of martensitic transformation (Martensite start, Ms), and improves hardenability. In addition, manganese is also a good deoxidizer and desulfurizer. The combined action of manganese and silicon is beneficial to reducing the oxygen content in the weld, and combines with sulfur to form manganese sulfide, preventing the formation of low-melting iron sulfide, preventing thermal cracks in the weld metal, and improving the weld's resistance to thermal cracks. Manganese and iron can form a solid solution, improving the strength and hardness of ferrite and austenite in steel. In the present invention, the mass percentage of metallic manganese is 2-5%, for example, the mass percentage of metallic manganese can be any value within the above range such as 2%, 4% or 5%.

[0024] Quartz: slag-forming agent. Its main component is silicon dioxide. When the silicon dioxide content increases, the weld surface becomes brighter and the slag color becomes darker, which is beneficial to the slag removal of the weld. However, when the silicon dioxide is added in excessive amounts, the low-temperature toughness of the weld will be affected. In the present invention, the mass percentage of quartz is 5% to 6%, for example, the mass percentage of quartz can be any value within the above range, such as 5%, 5.5% or 6%.

[0025] Rutile: slag-forming agent, the main component of slag, can significantly reduce the viscosity and surface tension of slag. The main component of rutile is titanium dioxide, and when there is more titanium dioxide in the slag, "short slag" is formed, which is beneficial to the formation of welds. In the present invention, the mass percentage of rutile is 25% to 30%, for example, the mass percentage of rutile can be any value within the above range such as 25%, 27% or 30%.

[0026] Ferro-molybdenum: Improves the hardenability, strength and ductility of steel. Molybdenum can eliminate or reduce the temper brittleness caused by other alloying elements, thereby greatly improving the impact toughness of steel. It is generally believed that 2% to 2.5% of ferro-molybdenum can obtain better comprehensive mechanical properties. For example, the mass percentage of ferro-molybdenum can be any value within the above range, such as 2%, 2.1%, 2.3% or 2.5%.

[0027] Fluorite: The main component of fluorite is calcium fluoride, which has the functions of slag formation, gasification, hydrogen removal, and adjustment of the pH value of welding slag. The mass percentage of fluorite in the present invention is 5-10%, for example, the mass percentage of fluorite can be any value within the above range such as 5%, 7%, 8% or 10%.

[0028] Potassium titanate: used as arc stabilizer for flux-cored welding wire, to increase arc voltage, increase arc blowing force, improve molten pool fluidity, and improve weld forming quality. The mass percentage of potassium titanate in the present invention is 5-10%, for example, the mass percentage of potassium titanate can be any value within the above range such as 5%, 6%, 8% or 10%.

[0029] Ferrotungsten: transition alloy element to weld metal. Tungsten is one of the important elements to improve the high temperature stability of steel. The proper addition of tungsten element is conducive to improving the impact toughness. The mass percentage of ferotungsten in the present invention is 1-2%, for example, the mass percentage of ferotungsten can be any value within the above range such as 1%, 1.3%, 1.5% or 2%.

[0030] Ferrovanadium: transition alloy element to weld metal. Vanadium is a strong ferrite forming element. Due to its strong binding force with carbon, nitrogen and oxygen, it will form corresponding compounds with strong stability. A small amount of vanadium can refine the grains of steel, thereby improving the strength and toughness of steel. The mass percentage of ferrovanadium in the present invention is 0.1-0.2%, for example, the mass percentage of ferrovanadium can be any value within the above range such as 0.1%, 0.15%, 0.18% or 0.2%.

[0031] Rare earth oxides: improve the structure of weld metal, refine grains, change the shape, size and distribution of inclusions, and improve the low-temperature impact toughness of weld metal. Rare earth not only has a good purification effect on weld metal, but also has a unique effect on improving the corrosion resistance of weld metal. Adding a trace amount of rare earth oxides to the flux core can improve the high-temperature corrosion resistance of the weld in a sulfur-containing atmosphere. The mass percentage of rare earth oxides in the present invention is 1%.

[0032] In one embodiment, the filling rate of the flux core in the cladding flux cored wire, i.e., the weight of the flux core, is 18-19% of the total weight of the flux core and the steel strip. For example, the filling rate of the flux core may be 18%, 18.5%, or 19%. The particle size of the flux core is controlled to be 40-80 meshes, such as 40 meshes, 60 meshes, or 80 meshes. In practical applications, the flux core is first configured according to the above component ratio, and then the flux core is filled into the steel strip at a filling rate of 18-19%.

[0033] See also Figure 1 The present invention provides a method for preparing a cladding flux-cored welding wire, comprising the following steps:

[0034] S1. Mix the components of the drug core evenly according to the above proportions;

[0035] S2, slitting, wrapping, cleaning and rolling the steel strip into a U-shaped groove;

[0036] S3, filling the drug core into the U-shaped groove;

[0037] S4, closing, reducing, drawing and winding the steel strip filled with the flux core to obtain the cladding flux cored welding wire.

[0038] In step S1, the components in the core are mixed and stirred uniformly according to the following proportions: 30-40% of metallic chromium, 2-5% of metallic manganese, 5-6% of quartz, 25-30% of rutile, 3-5% of ferrosilicon, 5-10% of potassium titanate, 5-10% of fluorite, 2-2.5% of ferromolybdenum, 0.1-0.2% of ferrovanadium, 1-2% of ferrotungsten, 1% of rare earth oxide, and the balance is iron powder;

[0039] In step S2, the steel strip is longitudinally cut into suitable sizes and then cleaned to remove impurities on the surface of the steel strip, and then the steel strip is rolled into a U-shaped groove. The steel strip used in the present invention is a carbon steel strip, preferably, the thickness × width of the carbon steel strip is 1.0 mm × 14 mm.

[0040] In step S3, the filling rate of the drug core is 18% to 19%. For example, the filling rate of the drug core can be any value within the above range, such as 18%, 18.5% or 19%.

[0041] In step S4, lubricating powder can be used to increase the lubricity during the wire drawing process, and preferably, graphite lubricating powder can be used.

[0042] The present invention also provides the use of the cladding flux-cored welding wire. Since the cladding flux-cored welding wire of the present invention has no pores in the weld without the protection of gas, flux, etc., and can ensure the weld formation and the required hardness, wear resistance and corrosion resistance, the cladding flux-cored welding wire can be used for seam welding of valve sealing surfaces.

[0043] The present invention is described in detail below through some specific examples. The drugs used in the following examples can all be obtained through common commercial means.

[0044] Example 1

[0045] The cladding flux-cored welding wire of this embodiment includes a steel strip and a flux core filled in the steel strip, wherein the flux core includes the following components by mass percentage: 40% metal chromium, 2% metal manganese, 5% quartz, 26% rutile, 4% 75# ferrosilicon, 10% potassium titanate, 6% fluorite, 2.5% ferromolybdenum, 0.1% ferrovanadium, 1% ferrotungsten, 1% rare earth oxide, and the balance is iron powder. The steel strip is a 1.0mm×14mm carbon steel strip, which is rolled into a U-shaped groove, and then the mixed flux core is filled into the U-shaped groove, and the filling rate of the flux core is 18%; then the welding wire is obtained by closing, reducing the diameter, drawing, and winding.

[0046] Example 2

[0047] The cladding flux-cored welding wire of this embodiment includes a steel strip and a flux core filled in the steel strip, wherein the flux core includes the following components by mass percentage: 38% metal chromium, 4% metal manganese, 5% quartz, 28% rutile, 3% 75# ferrosilicon, 6% potassium titanate, 8% fluorite, 2.3% ferromolybdenum, 0.15% ferrovanadium, 1% ferrotungsten, 1% rare earth oxide, and the balance is iron powder. The steel strip is a 1.0mm×14mm carbon steel strip, which is rolled into a U-shaped groove, and then the mixed flux core is filled into the U-shaped groove, and the filling rate of the flux core is 18.5%; then the welding wire is obtained by closing, reducing the diameter, drawing, and winding.

[0048] Example 3

[0049] The cladding flux-cored welding wire of this embodiment includes a steel strip and a flux core filled in the steel strip, wherein the flux core includes the following components by mass percentage: 34% metal chromium, 5% metal manganese, 6% quartz, 25% rutile, 5% 75# ferrosilicon, 5% potassium titanate, 10% fluorite, 2.4% ferromolybdenum, 0.2% ferrovanadium, 1.5% ferrotungsten, 1% rare earth oxide, and the balance is iron powder. The steel strip is a 1.0mm×14mm carbon steel strip, which is rolled into a U-shaped groove, and then the mixed flux core is filled into the U-shaped groove, and the filling rate of the flux core is 18.3%; then the welding wire is obtained by closing, reducing the diameter, drawing, and winding.

[0050] Example 4

[0051] The cladding flux-cored welding wire of this embodiment includes a steel strip and a flux core filled in the steel strip, wherein the flux core includes the following components by mass percentage: 30% metal chromium, 4% metal manganese, 6% quartz, 30% rutile, 5% 75# ferrosilicon, 6% potassium titanate, 5% fluorite, 2% ferromolybdenum, 0.2% ferrovanadium, 2% ferrotungsten, 1% rare earth oxide, and the balance is iron powder. The steel strip is a 1.0mm×14mm carbon steel strip, which is rolled into a U-shaped groove, and then the mixed flux core is filled into the U-shaped groove, and the filling rate of the flux core is 19%; then the welding wire is obtained by closing, reducing the diameter, drawing, and winding.

[0052] The cladding flux-cored welding wire of the present invention is used for all-position welding without the need for an external shielding gas. The welding wires provided in the above-mentioned Examples 1, 2, 3 and 4 are subjected to welding processability tests, weld metal chemical composition tests, wear resistance analysis tests and hardness tests according to relevant standards and specifications. The welding process performance is shown in Table 1, the weld metal chemical composition test results are shown in Table 2, the weld metal wear resistance test weight loss is shown in Table 3, and the hardness test results are shown in Table 4.

[0053] Table 1: Welding process performance

[0054]

[0055] Table 2: Chemical composition test results of weld metal (Wt.%)

[0056]

[0057] Table 3: Weld metal wear resistance weight loss test results

[0058] Quartz sand was used as the medium to carry out abrasive wear test. The wear time was 60 minutes and the weight loss was detected. The test results are as follows:

[0059] Test Project Example 1 Example 2 Example 3 Example 4 Weight loss (g) 0.23 0.25 0.24 0.25

[0060] Table 4: Weld metal hardness test results

[0061] Test Project Example 1 Example 2 Example 3 Example 4 Hardness HRC 54.1 52.4 53.5 50.8

[0062] The test results of Examples 1 to 4 show that the cladding flux-cored welding wire of the present invention can be used for all-position welding in the absence of gas and protective agent, and has stable arc during welding, small spatter, good welding process properties such as forming, slag coverage, and slag removal, and the deposited metal has high strength, high toughness, high wear resistance, and excellent corrosion resistance.

[0063] The surfacing flux-cored welding wire of the present invention improves the strength of the weld metal by adjusting alloy elements such as molybdenum, tungsten, and vanadium; the addition of rare earth oxides can improve the high-temperature corrosion resistance and impact toughness of the weld metal; the addition of quartz and rutile can form a short slag effect, which is beneficial to the formation of the weld; the application of potassium titanate ensures good weld formation, stable arc, smooth welding and other welding process properties. This welding wire is applied to the surfacing of the valve sealing surface, which can improve its surface wear resistance and corrosion resistance, thereby extending the service life of the valve. Therefore, the present invention effectively overcomes some practical problems in the prior art and has high utilization value and use significance.

[0064] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the technology may modify or change the above embodiments without violating the spirit and scope of the present invention. Therefore, all equivalent modifications or changes made by a person of ordinary skill in the art without departing from the spirit and technical ideas disclosed by the present invention should still be covered by the claims of the present invention.

Claims

1. A surfacing flux-cored welding wire, comprising a steel strip and a flux core filled in the steel strip, characterized in that: The core comprises the following components in percentage by mass: 30-40% metallic chromium, 2-5% metallic manganese, 5-6% quartz, 25-30% rutile, 3-5% ferrosilicon, 5-10% potassium titanate, 5-10% fluorite, 2-2.5% ferromolybdenum, 0.1-0.2% ferrovanadium, 1-2% ferrotungsten, 1% rare earth oxide, and the balance is iron powder.

2. The cladding flux-cored welding wire according to claim 1, characterized in that: The weight of the flux core in the surfacing flux-cored welding wire is 18% to 19% of the total weight of the surfacing flux-cored welding wire.

3. The cladding flux-cored welding wire according to claim 1, characterized in that: The particle size of the drug core is 40 to 80 meshes.

4. The cladding flux-cored welding wire according to claim 1, characterized in that: The ferrosilicon is 75# ferrosilicon, in which the silicon content is greater than or equal to 72%, the phosphorus content is less than or equal to 0.04%, and the sulfur content is less than or equal to 0.02%.

5. The cladding flux-cored welding wire according to claim 1, characterized in that: The fluorite has a calcium fluoride content of greater than or equal to 95%, a silicon dioxide content of less than or equal to 4.5%, a phosphorus content of less than or equal to 0.03%, and a sulfur content of less than or equal to 0.03%.

6. The cladding flux-cored welding wire according to claim 1, characterized in that: The rare earth oxide includes ceria.

7. The cladding flux-cored welding wire according to claim 1, characterized in that: The steel strip is a carbon steel strip.

8. A method for preparing a cladding flux-cored welding wire, characterized in that: The following steps are involved: Mixing the components in claim 1 uniformly to prepare a drug core; The steel strip is slitting, taping, cleaning, and then rolled into a U-shaped groove; Filling the drug core into the U-shaped groove; The steel strip filled with the flux core is closed, reduced in diameter, drawn and wound up to obtain the cladding flux cored welding wire.

9. Use of the cladding flux-cored welding wire according to claim 1, characterized in that: The surfacing flux-cored welding wire is used for surfacing welding of valve sealing surfaces.

Citation Information

Patent Citations

  • High-strength carbon dioxide protecting surfacing flux-cored wire

    CN102069322A

  • Abrasion-resistant surfacing flux-cored wire

    CN106238966A

  • Flux-cored wire for repairing hot forging die and using method of flux-cored wire

    CN113210930A